ANALISIS PENGARUH TRUST IN THE ORGANIZATION TERHADAP KNOWLEDGE SHARING DALAM DUNIA PERUSAHAAN : (KAJIAN EMPIRIS DAN TEORITIS DALAM IMPLEMENTASI) - Setiawati, Firda; Prahiawan, Wawan; Mumtazah, Liza (LPPM STIA Banten, 2024)
This study aims to investigate the influence of trust in organizations on knowledge sharing in the context of the corporate world. Trust in the organization was identified as a key factor that can influence knowledge sharing. In developing the research framework, qualitative methods were chosen with a focus on empirical analysis. Data was obtained through reference literature, reference books, Google Scholar. The research results show that trust in the organization has a positive effect on knowledge sharing between superiors, subordinates and colleagues. The conclusion of this research highlights the importance of trust in organizations within the company to share knowledge with fellow employees. Research implications of the influence of trust in organizations on knowledge sharing in the corporate world (empirical and theoretical studies in implementation)